Rebooting policy analysis strengthening the foundation, expanding the scope - Linquiti, Peter D. (Thousand Oaks, California Sage Publications, 2023)
Rebooting Policy Analysis: Strengthening the Foundation, Expanding the Scope is a savvy introduction to policy analysis that gets students thinking, not just about how decisions should be made, but how they are made. The text highlights practical skills needed to advise decision-makers on matters of public policy in ways that are well-informed and solutions-oriented, while managing limitations like time, resources, and information. In a world that has become increasingly complex and partisan, the strength of policy analysis rests not only in its classical academic methods, but on the development of a practical, analytic mindset.
Part I: The Classical Models and their Limitations -- Chapter 1 Thinking about the Future: Prospective Policy Analysis -- Chapter 2 Thinking About the Past: Retrospective Program and Impact Evaluation -- Chapter 3 Obstacles to Using Classical Policy Analysis Models in the Real World -- Part II: Introduction: Thinking Clearly -- Chapter 4 Using Metacognition to Check Your Own Biases & the Biases of Others -- Chapter 5 Using Logic to Identify Tentative Truths -- Chapter 6 Collecting and Evaluating Evidence for Use in Policy Analysis -- Chapter 7 The Mindset of an Effective Policy Analyst -- Part III: Looking at Policy Issues Through Different Lenses -- Chapter 8 The Equity Lens -- Chapter 9 The Economics Lens -- Chapter 10 The Political and Institutional Lenses -- Chapter 11 The Legal, Sustainability, and Science and Technology Lenses -- Part IV: The Building Blocks of Policy Analysis -- Chapter 12 Incorporating Systems Thinking in Policy Analysis -- Chapter 13 Using Policy Analysis to Visualize the Future -- Chapter 14 Designing and (Re)Designing Public Policies -- Chapter 15 Having an Impact While Preserving Your Integrity. -- Appendix 15-A Ethics Codes from Four Organizations -- References -- Index
Includes bibliographical references (pages 555-573) and index.
Keywords: Policy sciences -- Methodology